Post-target produced [18F]F2 in the production of PET radiopharmaceuticals. - Forsback S; Solin O (De Gruyter, 2022)
Electrophilic radiofluorination was successfully carried out in the early years of PET radiochemistry due to its ease and fast reaction speed. However, at the present, the use of electrophilic methods is limited due to low specific activity (SA). Post-target produced [F-18]F-2 has significantly higher SA compared to other electrophilic approaches, and it has been used in the production of clinical PET radiopharmaceuticals at the Turku PET Centre for years. Here, we summarize the synthesis and use of these radiopharmaceuticals, namely [F-18]FDOPA, [F-18]CFT, [F-18]EF5 and [F-18]FBPA.